On the Role of Radioactive Decays in Powering Gamma Rays and X-Rays from Novae - Livio, Mario; Mastichiadis, Apostolos; Oegelman, Hakki; Truran, James W. (1992)
Existing models for X-ray emission from novae in outburst encounter several difficulties. The X-ray flux that may be expected to result from Compton degradation of gamma rays produced by radioactive decays is calculated. It is demonstrated that radioactive decays of Na-22 may play an interesting role in the production of hard X-rays, particularly in novae enriched in oxygen, neon, and magnesium.
Keywords: Abundances; Astrophysics; CATACLYSMIC VARIABLES; Gamma Ray Astronomy; Light Curve; Novae; Nuclear Astrophysics; Nuclear Fusion; Nuclear Reactions; Nucleosynthesis; Radioactive Decay; Sodium 22; STARS: NOVAE; stellar evolution; Stellar Models; X Ray Stars; X-Rays: Stars